Tri Nga (Ngerti, Ngrasa, Nglakoni) Based Teaching Practice Assessment Model - Nasyariah Siregar; Risnita Risnita; Ana Fitrotun Nisa; Fia Alifah Putri (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to develop a more comprehensive assessment model in teaching practice and to support the realization of prospective teachers/educators who are skilled at teaching through PPL/PLP activities. This research method used research & development model of Borg and Gall with 10 stages. The data collection process was carried out by tests, interviews, questionnaires, observation and documentation. Technique of data analysis that used in this study is descriptive statistics. The result of the study showed that there are three phases in the implementation of the assessment model. First, Got It; students have knowledge related to teaching practice activities that are assessed through tests (objectives and descriptions). Second, feel; the ability to internalize the personality and social competencies that are assessed through observation sheets and thirdly, Acting; performing with complete sincerity which is assessed through performance. With a score of 89.36 from the three validators, this Tringa-based assessment model is suitable for use in teaching practice.